1989
DOI: 10.1159/000158768
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Rupture of the Internal Elastic Lamina in the Rat: The Manifestation of a Genetically Determined Factor Which May Be Linked to Vascular Fragility

Abstract: The spontaneous rupture of the internal elastic lamina (IEL) in various arteries occurs to different extents in different rat strains. We have quantified this phenomenon in the caudal and renal arteries and abdominal aorta in two normotensive inbred strains: the Brown Norway (BN) and Long Evans (LE) strains. At 5 weeks of age, BN rats of both sexes exhibited small numbers of interruptions in the IEL of the caudal artery, whereas LE rats did not. Postpubertal male and female BN rats presented large numbers of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
79
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(88 citation statements)
references
References 19 publications
9
79
0
Order By: Relevance
“…11 Our present data on spontaneously hypertensive rats are in agreement with these previous results, suggesting that a high propensity for the spontaneous rupture of the arterial internal elastic lamina is related to increased vascular fragility, which under adverse conditions such as hypertension may lead to pathologic events.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…11 Our present data on spontaneously hypertensive rats are in agreement with these previous results, suggesting that a high propensity for the spontaneous rupture of the arterial internal elastic lamina is related to increased vascular fragility, which under adverse conditions such as hypertension may lead to pathologic events.…”
Section: Discussionsupporting
confidence: 93%
“…10 In addition, the greater BAPN-induced premature rupture of the internal elastic lamina in the caudal artery of SHRSP than of SHR suggests that the inhibition of lysyl oxidase during growth had a greater adverse effect on the internal elastic lamina of the caudal artery in SHRSP. Previous studies have also reported different sensitivities to BAPN treatment, concerning both aortic aneurysm formation and rupture 24 and rupture of the internal elastic lamina, 11 in different substrains. In experiments in which BAPN was given from 5 or 10 weeks of age, most rats died of aortic rupture and not of stroke.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…16 According to our results, it is possible that BN alleles leading to a depletion in aortic elastin content may impact on blood pressure QTL detection and significance. In addition, the BN rat shows evidence of vascular abnormalities, including susceptibility to spontaneous ruptures of the abdominal aortic IEL, 7 which the LOU strain is devoid of. We particularly focused the genome-wide scan in the BNϫLOU cross on regions of rat chromosomes 5 and 10, which were previously associated with susceptibility to IEL rupture in a BNϫGH cross, 8 to test a possible relationship between this phenotype and variations in components of the aortic extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…7 The aortic elastin deficit in the BN rat is, at least in part, caused by decreased tropoelastin synthesis during the period of rapid growth. 5 Because the elastin gene polymorphism explains only a small part of differences between parental strains, it is thus probable that other genes account for the major proportion of the interstrain differences in aortic elastin content.…”
mentioning
confidence: 99%